On asymptotic expansion of the convolution of n multi-dimensional distribution functions - Bikelis, A.; Mogyorödi, J. (Lithuanian Mathematical Journal, 1970)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. Бикялис, И. Модеруди. Об асимптотическом разложении для n-кратных сверток k-мерных распределений A. Bikelis, J. Moderudi. n kartų kartotinės k-mačio pasiskirstymo kompozicijos asimptotinis išdėstymas